Analysis of dispensation of major medicinal products available by the Popular Pharmacy Program of Brazil in a pharmacy (Research, Society and Development, 2020)
The Popular Pharmacy Program of Brazil (PFPB) is an innovation for the public policy of pharmaceutical assistance, bringing several benefits to the population suffering from chronic diseases and who need to use continuous medicines and often cannot afford the treatment. of a particular. The article aimed to characterize the main drugs dispensed in a pharmacy that provides a service of the Popular Pharmacy of Brazil, also considering the main therapeutic indications associated with the use of the program. This will be a descriptive field study of quantitative exploratory nature, in which the main medicines available through the PFPB were listed. The survey was conducted through a visit to a specific pharmacy in September, in which a list was provided for information. The sample consists of the main drugs present in the computerized system of this pharmacy. Where were included in the study only groups of drugs, whether with free service or copayment. All items that are available through the PFPB but are not considered medications, such as geriatric diapers, were excluded from the study. It is concluded that the study brings relevant information about the drugs available to the population considering the aspects of pharmaceutical treatment of PFPB.